2007
DOI: 10.2174/092986607780090883
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Expression and Purification of an Analgesic Peptide from Buthus martensii Karch

Abstract: BmK AngM1, a scorpion peptide isolated from Buthus martensii Karch was reported to exhibit potential analgesic effect. But the relative low content of this toxin in crude venom limits its further characterization. In this study, we constructed an expression vector and transformed into E.coli. The BmK AngM1 was expressed as a fusion protein in the soluble fraction and was purified by Nickel affinity chromatography. Subsequently, the purified fusion protein was cleaved by enterokinase and was further purified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Similar results were obtained in our experiment. The production of rBmK AngM1 in P. pastoris was above 500 mg/l, which was more than three times of that in E. coli (Cao et al 2007). Bioactivity assay indicated that the analgesic effect of rBmK AngM1 expressed in P. pastoris was slightly less than that of the natural toxin but much better than that expressed in E. coli.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similar results were obtained in our experiment. The production of rBmK AngM1 in P. pastoris was above 500 mg/l, which was more than three times of that in E. coli (Cao et al 2007). Bioactivity assay indicated that the analgesic effect of rBmK AngM1 expressed in P. pastoris was slightly less than that of the natural toxin but much better than that expressed in E. coli.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, it is important to develop new strategies for BmK AngM1 production. The previous attempt was made in Escherichia coli to obtain recombinant BmK AngM1 (rBmK AngM1) (Cao et al 2007). But the inconvenient purification and relatively low production of rBmK AngM1 from E. coli limited its application.…”
Section: Introductionmentioning
confidence: 99%
“…This strain produced high yields of heterologous secreted proteins [ 49 ]. Heterologous proteins developed as inclusion bodies in E. coli are inert, composite, and insoluble and typically exhibit non-native intra- and inter-molecular disulfide bonds and rare free cysteines [ 50 ]. Such bodies must be separated from the cell to derive the active protein along with the proteins solubilized by denaturants, and disulfide bonds must be extracted using reduction agents.…”
Section: Host Strains For the Overexpression Of Target Proteinsmentioning
confidence: 99%
“…Thus, affinity tags are usually chosen depending on qualitative knowledge. To resolve this absence of a standardized analysis for affinity tags, we have previously measured the quality, yield, and expense by using two protein fusion and six short peptide affinity tags to purify two E. coli -expressed proteins [ 50 ]. We evaluated the capacity of the affinity resins to purify labeled proteins from extracts derived from yeast, Drosophila , and HeLa cells.…”
Section: Purificationmentioning
confidence: 99%